How to produce leucaena leafmeal - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Guide to the production of Leucaena leafmeal in Grenada Grenada National Science and Technology Council (NSTC)